2016
DOI: 10.1021/acs.jpclett.6b00999
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural and Optical Properties of Organometal Halide Perovskite-Based Formamidinium Lead Bromide

Abstract: Organometal halide perovskites (OMHPs) are attracting an ever-growing scientific interest as photovoltaic materials with moderate cost and compelling properties. In this Letter, pressure-induced optical and structural changes of OMHP-based formamidinium lead bromide (FAPbBr3) were systematically investigated. We studied the pressure dependence of optical absorption and photoluminescence, both of which showed piezochromism. Synchrotron X-ray diffraction indicated that FAPbBr3 underwent two phase transitions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
250
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(277 citation statements)
references
References 48 publications
26
250
1
Order By: Relevance
“…[12] The hydrophobic molecules in the organic layers effectively improve the moisture resistance compared to the 3D perovskite, which solves the main obstacle of 3D OIHPs. [21][22][23][24][25] For example, Wang et al studied the structural transition and photoresponse of CH 3 NH 3 PbBr 3 (MAPbBr 3 ) under pressure. [15,16] The alternating layers of 2D lead-halide perovskites induce an exceptionally large exciton binding energy [15,17] and a wide band gap in contrast to 3D lead-halide perovskites, which limits its optical performance.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[12] The hydrophobic molecules in the organic layers effectively improve the moisture resistance compared to the 3D perovskite, which solves the main obstacle of 3D OIHPs. [21][22][23][24][25] For example, Wang et al studied the structural transition and photoresponse of CH 3 NH 3 PbBr 3 (MAPbBr 3 ) under pressure. [15,16] The alternating layers of 2D lead-halide perovskites induce an exceptionally large exciton binding energy [15,17] and a wide band gap in contrast to 3D lead-halide perovskites, which limits its optical performance.…”
mentioning
confidence: 99%
“…[15,16] The alternating layers of 2D lead-halide perovskites induce an exceptionally large exciton binding energy [15,17] and a wide band gap in contrast to 3D lead-halide perovskites, which limits its optical performance. Wang et al observed that pressure can efficiently reduce the band gap of formamidinium lead bromide (FAPbBr 3 ) [22] and methylammonium lead chloride Due to their superior optical and electronic properties and good stability, 2D organic-inorganic halide perovskites (OIHPs) exhibit strong potential for optoelectronic applications. Therefore, reducing the band gap and prolonging the carrier lifetime are two critical issues to be considered when improving the performance of 2D lead-halide perovskites for practical applications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2D nanoplates and 1D nanowires can be formed by ligand engineering, reaction‐temperature engineering, purification, ultrasonication, A‐site‐cation engineering, or by using additives . Furthermore, the synthesized MHP NCs can be also post‐transformed from 3 nm thick CsPbBr 3 nanosheets to Pb nanoparticle (NP)–CsPbBr 3 nanocomposites by electron beams, from 2D CsPbBr 3 nanoplatelets to larger structures such as nanobelts or square‐shaped nanodisks by photoirradiation, or from cubic phase to orthorhombic phase in FAPbBr 3 crystals by pressure …”
Section: Colloidal Nanocrystals and Light‐emitting Diodesmentioning
confidence: 99%